2012
DOI: 10.4103/0972-6748.119638
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting amisulpride with clozapine had led to unmasking of akathisia

Abstract: Amisulpride is a newer antipsychotic, which is very effective on its own, as well as augmenting other antipsychotic clozapine, which is an effective molecule for treatment resistant schizophrenia. In most cases, amisulpride is added on, in partial responders to clozapine. Here a case is reported where clozapine was added on, in an amisulpride partial responder but this produced side effect and had to be discontinued. The case later responded to clozapine alone. It has been discussed about possible reasons of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In terms of spontaneous case report's authors have described acute and tardive nocturnal akathisia, akathisia in children and akathisia on augmentation of clozapine with amisulpride (for details see). [ 5 ] Our case description adds to these findings.…”
Section: Discussionsupporting
confidence: 53%
“…In terms of spontaneous case report's authors have described acute and tardive nocturnal akathisia, akathisia in children and akathisia on augmentation of clozapine with amisulpride (for details see). [ 5 ] Our case description adds to these findings.…”
Section: Discussionsupporting
confidence: 53%
“…This correlation has been reviewed in the literature and the results are debated, as plasma concentration, rather than clozapine daily dose, seems to have an impact on metabolic changes [ 42 ]. One study confirms a high prevalence of metabolic side effects with clozapine and suggested higher clozapine level and certain pharmacogenetic markers as important predictors of metabolic syndrome [ 43 ].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, consideration must be given to drug-to-drug interactions when using multiple agents. Ray and Munshi presented a case where adding low-dose clozapine to baseline amisulpride treatment aggravated existing akathisia, with new onset dystonia and hypersalivation [ 40 ]. The authors postulated that these adverse effects were due to increased serum amisulpride levels due to interaction with clozapine, which has been reported previously [ 41 ].…”
Section: Discussionmentioning
confidence: 99%